A cost-effectiveness analysis of the integration of robotic spine technology in spine surgery - Menger, Richard Philip; Savardekar, Amey R.; Farokhi, Frank; Sin, Anthony (Neurospine, 2018)
We investigate the cost-effectiveness of adding robotic technology in spine surgery to an active neurosurgical practice. The time of operative procedures, infection rates, revision rates, length of stay, and possible conversion of open to minimally invasive spine surgery (MIS) secondary to robotic image guidance technology were calculated using a combination of institution-specific and national data points. This cost matrix was subsequently applied to 1 year of elective clinical case volume at an academic practice with regard to payor mix, procedural mix, and procedural revenue. A total of 1,985 elective cases were analyzed over a 1-year period; of these, 557 thoracolumbar cases (28%) were analyzed. Fifty-eight (10.4%) were MIS fusions. Independent review determined an additional ~10% cases (50) to be candidates for MIS fusion. Furthermore, 41.4% patients had governmental insurance, while 58.6% had commercial insurance. The weighted average diagnosis-related group reimbursement for thoracolumbar procedures for the hospital system was calculated to be $25,057 for Medicare and $42,096 for commercial insurance. Time savings averaged 3.4 minutes per 1-level MIS procedure with robotic technology, resulting in annual savings of $5,713. Improved pedicle screw accuracy secondary to robotic technology would have resulted in 9.47 revisions being avoided, with cost savings of $314,661. Under appropriate payor mix components, robotic technology would have converted 31 Medicare and 18 commercial patients from open to MIS. This would have resulted in 140 fewer total hospital admission days ($251,860) and avoided 2.3 infections ($36,312). Robotic surgery resulted in immediate conservative savings estimate of $608,546 during a 1-year period at an academic center performing 557 elective thoracolumbar instrumentation cases. Application of robotic spine surgery is cost-effective, resulting in lesser revision surgery, lower infection rates, reduced length of stay, and shorter operative time. Further research is warranted, evaluating the financial impact of robotic spine surgery.